Power of Productivity:Wealth Poverty and the Threat to Global Stability - William W Lewis; LEWIS (William W) (Chicago The University of Chicago Press, 1942)
The disparity between rich and poor countries is the most serious, intractable problem facing the world today. Chronic poverty affects more than the citizens and economies of these nations; it threatens global stability as the pressures of immigration become unsustainable and rogue nations seek power and influence through extreme political and terrorist acts. For decades, a vast array of international institutions has pumped billions of dollars into these nations in an attempt to remedy their ills through the development of technological infrastructures, educational systems, and health care programs. Yet despite this infusion of capital and attention, roughly five billion of the world's six billion people continue to live in poverty. What isn't working? And how can we fix it? "The Power of Productivity" provides powerful and controversial answers to these questions. William Lewis, director emeritus of the McKinsey Global Institute, draws on extensive microeconomic studies of thirteen nations - conducted over twelve years by the Institute itself - to counter virtually all prevailing wisdom about how best to ameliorate economic disparity. The key to reducing economic inequalities between rich and poor countries, argues Lewis, is productivity and its links to competition and consumption. Diagnosing problems and offering solutions, "The Power of Productivity" will inform political and economic debate throughout the world for years to come.
Keywords: Industrial Productivity; Economic Policy; Investments; Wealth; Poverty; Economic Stabilization; Consumption; Microeconomics; Economic Development